Study of hematological parameters in the early diagnosis of neonatal sepsis in tertiary care center in Jharkhand - Lal, Swati; Shankar, Mani; Adhikari, Bankim Chandra; Chaudhary, Anil Kumar (Indian Journal of Child Health, 2020)
Background: Bacterial sepsis is a major cause of morbidity and mortality in newborns. Probable sepsis is a clinical and laboratory finding consistent with bacterial infection without a positive culture. Objectives: The objectives of the study were to study and determine the predictive value of hematological parameters in the early diagnosis of neonatal sepsis at a tertiary care center in Jharkhand. Materials and Methods: This was a prospective study conducted from July 2016 to June 2017 in a tertiary care teaching hospital in Jharkhand. A total of 110 neonates admitted in neonatal intensive care unit of the hospital, with either clinical suspicion of sepsis or having predisposing perinatal factors for sepsis, were included in the study. In this study, hematological scoring system (HSS) along with clinical profile of patient and sepsis screening tests was studied. Sensitivity, specificity, and positive predictive value (PPV) of each parameter were studied and analyzed. Results: Out of 46 cases with culture-proven sepsis, 40 (86.95%) infants had score ?5 and 6 (13.04%) had scores 3–4. HSS had a sensitivity of 86.95% and a specificity of 78.12%. HSS had PPV of 74.07%. Male babies were observed to be affected more than female babies. Conclusion: As no single individual hematological parameter is superior to other in predicting neonatal sepsis, a combination of these parameters in the form of HSS and C-reactive protein has been recommended. We conclude that HSS is a useful test to distinguish the infected from non-infected neonates.